Stock Price Management and Share Issuance: Evidence from Equity Warrants - Barth, Mary E.; Gee, Kurt H.; Israeli, Doron; Kasznik, Ron (The Accounting Review, 2021)
ABSTRACT We investigate whether firms manage stock prices in anticipation of share issuance. Warrant exercise results in share issuance and warrant expiration dates are fixed years in advance, which precludes market timing. We predict firms manage stock prices to prevent (induce) warrant exercise when exercise is dilutive (anti-dilutive) to existing shareholders. To test our prediction, we examine stock returns around warrant expiration dates. We find that the difference between out-of-the-money (OTM) and in-the-money (ITM) firms' return patterns (i.e., post-expiration minus pre-expiration returns) is positive, and OTM (ITM) firms' return pattern is positive (negative). Return patterns of three sets of pseudo warrant firms differ from patterns of warrant firms. Return patterns are stronger when more feasible price changes are required to affect warrant expiration status, and firm-issued news items is a mechanism for price management. Thus, our findings provide evidence that firms engage in stock price management in anticipation of share issuance. JEL Classifications: G14; G15; G32; M41.